2021
DOI: 10.1177/00333549211055137
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 Seroprevalence by Community Survey and Residual Specimens, Denver, Colorado, July–August 2020

Abstract: Objectives The number of SARS-CoV-2 infections is underestimated in surveillance data. Various approaches to assess the seroprevalence of antibodies to SARS-CoV-2 have different resource requirements and generalizability. We estimated the seroprevalence of antibodies to SARS-CoV-2 in Denver County, Colorado, via a cluster-sampled community survey. Methods We estimated the overall seroprevalence of antibodies to SARS-CoV-2 via a community seroprevalence survey in Denver County in July 2020, described patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The findings of this study demonstrated no association between the presence of TGA and previous SARS-CoV-2 infection in a large sample of Colorado children. Our study showed high rates of SARS-CoV-2 infections observed in Colorado children representing racial/ethnic minorities, especially Hispanics, consistent with previous reports (13). To our knowledge, this is the first large-scale analysis of CDA during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study demonstrated no association between the presence of TGA and previous SARS-CoV-2 infection in a large sample of Colorado children. Our study showed high rates of SARS-CoV-2 infections observed in Colorado children representing racial/ethnic minorities, especially Hispanics, consistent with previous reports (13). To our knowledge, this is the first large-scale analysis of CDA during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Convenience sampling at highly visited community locations such as essential businesses may be an attractive alternative to structured sampling in this important population, similar to sampling approaches developed to study so-called hidden populations 25. Finally, two recent studies have shown that, in some contexts, SARS-CoV-2 seroprevalence studies obtained via convenience sampling closely approximate those obtained via randomised, representational sampling,26 27 although additional comparisons in other contexts are needed.…”
Section: Discussionmentioning
confidence: 99%